2020
DOI: 10.1002/tox.22902
|View full text |Cite
|
Sign up to set email alerts
|

Methoxytetrahydro‐2H‐pyran‐2‐yl)methyl benzoate inhibits spinal cord injury in the rat model via PPAR‐γ/PI3K/p‐Akt activation

Abstract: Spinal cord injury (SCI) is the most commonly seen trauma leading to disability in people worldwide. The purpose of current study was to determine the protective effect of methoxytetrahydro-2H-pyran-2-yl)methyl benzoate (HMPB) on SCI in rat model. TUNEL staining was used to examine apoptotic changes in spinal cord of SCI rats. The ELISA kits were employed to assess inflammatory processes and oxidative factors in the spinal cord tissues. Behavioral changes in SCI rats were assessed using Basso, Beattie, and Bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Spinal cord injury (SCI) is a serious neurological disorder characterized by complete or partial impairment of motor function leading to loss of motor function, which has caused chronic impairment and disability [ 1 , 2 ]. SCI contains primary and secondary injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a serious neurological disorder characterized by complete or partial impairment of motor function leading to loss of motor function, which has caused chronic impairment and disability [ 1 , 2 ]. SCI contains primary and secondary injuries.…”
Section: Introductionmentioning
confidence: 99%
“…The antiinflammatory mechanism of PPARα is primarily associated with the activation of the nuclear factor erythroid 2-related factor 2 (Nrf2) and the inhibition of NF-κB. The previous studies have identified that PPARα plays crucial role and is widely involved in the progression of SCI [12][13][14]. Importantly, the endogenous fatty acid palmitoylethanolamide (PEA), as a PPARα agonist, is one of the members of N-acylethanolamines family [15].…”
Section: Introductionmentioning
confidence: 99%